The Therapeutic Role of the Monastic Environment for Individuals with ASC: The Case of Hildegard of Bingen and her Lingua Ignota - Janko Nešić; Vanja Subotić; Petar Nurkić (Eidos. A Journal for Philosophy of Culture, 2024)
The aim of this paper is to show how a monastic environment can be regarded as providing shelter for individuals with autism spectrum condition in the Middle Ages. By drawing on the recent literature in the history of medicine that traces the signs and symptoms of ASC in Hildegard of Bingen, a Benedictine abbess from the twelfth century, we will turn to her invented language Lingua Ignota as a source of justification for her diagnosis and as one manner in which she managed her neurodivergence. We invoke contemporary embodied and ecological approaches to cognition and its impairments in order to understand how the medieval monastic socio-material niche could have played a crucial role in the inclusion of individuals with ASC, and as providing a therapeutic environment.